Підходи до нормування економічних показників - Волощук, Р.В. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2009)
This article studies the methods of normalization of indicators characterizing complex systems (economic, environmental) as well as being used in tasks of estimation of economical or technological security. Weaknesses and strengths of each approach are identified . Keywords: indicator normalization, complex system, aggregated indicator, integral index, investment security.